The environmental risk and water pollution: A review from the river basins around the world - Muhammad Barzani, Gasim; Mohd Ekhwan, Toriman (2013)
"Water for Life" has declared as the International Decade (2005 to 2015) for Action for water by the United Nations General Assembly in 2005. Because of the rapid increase in demand for water, and increase in occurrences of pollution of numerous water sources, environmental risks to humans and other life beings are enhanced. Due to changes in the quantity and quality of water, some environmental disasters are causing stress and hardships in a river basin in around the world. This paper reviews empirical evidence on the impact of polluted river water in the context of environmental risk as well as Ecological Risk. A rigorous survey has done on the existing literature of environmental risk and water pollution in respect of ecological, social and economic boundaries in the river basin area. The review findings concluded that polluted river water are seriously caused for hampering of the Sustainable Development (SD) especially in the context of sustainable development, ecosystems change, sustainable livelihoods, land cover, ecosystems, environmental sensitivity, biodiversity and geodiversity as well as social and economic arena in a river basin over the world. The study has drawn Necessary recommendations & policy considerations which would be raised and highlighted for implementation by policy and decision makers throughout the study.